EFEKTIVITAS EDUKASI 3M PLUS TERHADAP ANGKA BEBAS JENTIK DI WILAYAH KERJA PUSKESMAS BERINGIN JAYA - Sibuea, Bonar Pandapotan; PURBA, Seri Ulina (IKES Payung Negeri Pekanbaru, 2025)
Dengue Hemorrhagic Fever (DHF) is an infectious disease transmitted through the bites of Aedes aegypti and Aedes albopictus mosquitoes, with a high case burden in Indonesia, including in South Labuhanbatu Regency. One of the efforts to control DHF is through Mosquito Nest Eradication (PSN) using the 3M Plus method, which aims to increase the Mosquito-Free Rate (ABJ) as an indicator of vector control success. This study aims to analyze the effectiveness of PSN 3M Plus education on increasing ABJ in the working area of Beringin Jaya Health Center. The method used is quantitative with a quasi-experimental one-group pretest-posttest design. The research sample consisted of 100 households selected according to inclusion criteria, with an initial measurement of the presence of mosquito larvae (pretest), followed by an intervention in the form of 3M Plus PSN education through outreach, mutual cooperation, and cadre assistance, as well as a re-measurement (posttest). The research results showed that before the intervention, mosquito larvae were found in 48% of homes, while 52% were free of larvae. After the intervention, the ABJ increased significantly to 100% with a p-value of 0.0001. These findings demonstrate that 3M Plus PSN education is effective in increasing community awareness and behavior towards dengue prevention, thus it can be used as a sustainable promotional and preventive strategy in vector control.